2020
DOI: 10.1093/bioinformatics/btaa725
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into SARS-CoV-2 epidemic via revealing the features of SARS-CoV-2 coding proteins and host responses upon its infection

Abstract: There are seven known coronaviruses that infect humans: four mild coronaviruses, including HCoV-229E, HCoV-OC43, HCoV-NL63, and HCoV-HKU1, only cause mild respiratory diseases, and three severe coronaviruses, including SARS-CoV, MERS-CoV and SARS-CoV-2, can cause severe respiratory diseases even death of infected patients. Both infection and death caused by SARS-CoV-2 are still rapidly increasing worldwide. In this study, we demonstrate that viral coding proteins of SARS-CoV-2 have distinct features and are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The 8th key protein ATM plays a central role in responses to various forms of DNA damage, immunodeficiency, virus integration, virus replication and virus infection [ 95 , 96 ]. The 9th key gene CCT2 is a potential drug target against SARS-COV-2 infections [ 93 , 97 , 98 ]. The 10th key gene ETS1 is associated with some potential SARS-COV-2 infections related molecular pathways [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 8th key protein ATM plays a central role in responses to various forms of DNA damage, immunodeficiency, virus integration, virus replication and virus infection [ 95 , 96 ]. The 9th key gene CCT2 is a potential drug target against SARS-COV-2 infections [ 93 , 97 , 98 ]. The 10th key gene ETS1 is associated with some potential SARS-COV-2 infections related molecular pathways [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated peripheral neutrophil counts are associated with cytokine storms and massive neutrophil infiltration of the lungs, resulting in severe lung lesions ( Channappanavar and Perlman, 2017 ). A recent study revealed the distinct characteristics of the viral coding proteins of SARS-CoV-2, and infection with the virus could induce enrichment of host responsive genes related to the overactivation of neutrophils ( Qin et al., 2021 ). This finding suggested the crucial roles of neutrophil dysfunction in COVID-19, which was also found to be a distinct inflammatory feature related to the pathogenesis of SARS and MERS ( Channappanavar and Perlman, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of host responsive genes (HRG) for SARS-CoV-2 showed that they are especially enriched in IL-17 signalling, cytokine-cytokine receptor interaction, and NF-kB pathways, among other proceses ( Qin et al, 2020 ). Research has indicated that the NF-kB pathway, which is induced by several mediators, plays a role in cytokine storm ( Mozafari et al, 2020 ).…”
Section: Mainmentioning
confidence: 99%
“…The percentage of neutrophils and the absolute value of neutrophils in patients with critical illness and death were always higher than those of non-critically ill patients and surviving patients. This indicates that continued excessive activation of neutrophils plays a crucial role in SARS-CoV-2, leading to severe illness and death ( Qin et al, 2020 ).…”
Section: Leukocyte-associated Immunoglobulin-like Receptor-1mentioning
confidence: 99%